Machines and apparatus for testing and measuring (MENA Report, 2013)
(c) 2012 Al Bawaba (Albawaba.com) Disclaimer: The above text is Machine Translated. For accuracy, please refer to the text in the original language in the attached document. For any assistance, please feel free to contact customercare@tendersinfo.com